RELATIONSHIP OF SOCIAL MARKETING WITH PRODUCT POSITIONING: A FIELD STUDY IN IRAQI STATE COMPANY OF FERTILIZERS INDUSTRY - Sarmad Hamza Jassim (Galaxy International Interdisciplinary Research Journal, 2023)
A purpose of this research is enhance product positioning through company’s commitment to social marketing, as Iraqi State Company of Fertilizers Industry was chosen to test correlation and influence between social marketing and product positioning with sample size of (51) managers. Majored conclusion is product positioning in the industry in which company operates can be improved if company applies aspects that competitors did not care about such as social marketing. Majored recommendation is the company can achieve leadership in its industry when it guarantees customer loyalty and has a large market share, a company may be achieving this when reinforce social marketing which requires achieving economic business, human rights and natural environment.